Proces zarządzania kosztami w zakładzie ubezpieczeń - Chmielowiec-Lewczuk, Magdalena (Cost management process in insurance companies, 2006)
Cost management is very important part of management in each company, especially in insurance companies which should concentrate on reaching satisfied results. Management accounting is information system which generates data base for cost management. This process contains such tasks as: finding out common elements for the chosen strategy of insurance company and costs reduction, preparing the partition strategic tasks on three insurance company activity areas, selection and elaboration proper cost accounting system, preparation costs budgeting, monitoring actions and operations, preparing costs calculation report according to received early costs classification, control and deviations analysis, estimation of cost management process application.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 43-49